(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the historical development of sheep breeding, particularly karakul farming, in Bukhara region during 1992-1994. It highlights the agrarian reforms implemented in the early years of Uzbekistan’s independence, changes in ownership forms, and the establishment of ферmer farms that significantly influenced the livestock sector. Based on scientific sources, the article examines the economic importance of karakul breeding in Bukhara region, breeding activities, production processes, and export potential.